The Friday evening case of acute kidney injury: a crystal dilemma - Guzzo, Gabriella (Clin Kidney J, 2018)
We report a case of acute kidney injury (AKI) induced by amoxycillin crystalluria suggested by massive amounts of urinary crystals of unusual morphology. This hypothesis was further reinforced by a particular solubility pattern when the urine sample was exposed to various temperatures, alkali, acids and alcohol. We therefore suspended amoxycillin, which produced a rapid and complete recovery of kidney function. Infrared spectroscopy later confirmed the amoxycillin composition of the crystals. Since infrared spectroscopy is not easily available, we propose that these solubility tests of urinary crystals be used as a first-step investigation when amoxycillin crystalluria is suspected.